Inflammation markers and their trajectories after deep vein thrombosis in relation to risk of post‐thrombotic syndrome. (10th February 2015) - Rabinovich, A.; Cohen, J. M.; Cushman, M.; Wells, P. S.; Rodger, M. A.; Kovacs, M. J.; Anderson, D. R.; Tagalakis, V.; Lazo‐Langner, A.; Solymoss, S.; Miron, M. J.; Yeo, E.; et al.
Summary Background Post‐thrombotic syndrome (PTS) is a frequent chronic complication of deep vein thrombosis (DVT). Objective In the BioSOX study, we investigated whether inflammation markers predict the risk of PTS after DVT. Methods We measured C‐reactive protein (CRP), ICAM‐1, interleukin (IL)‐6, and IL‐10, at baseline, and 1 month and 6 months after a first proximal DVT, among 803 participants in the SOX trial. Participants were prospectively followed for 24 months for development of PTS. Results Median CRP levels at 1 month, ICAM‐1 levels at baseline, 1 month and 6 months, IL‐6 levels at 1 month and 6 months and IL‐10 levels at 6 months were higher in patients who developed PTS than in those who did not. Multivariable regression with the median as a cutoff showed risk ratios (RRs) for PTS of 1.23 (95% confidence interval [CI] 1.05–1.45) and 1.25 (95% CI 1.05–1.48) for ICAM‐1 at 1 month and 6 months, respectively, and 1.27 (95% CI 1.07–1.51) for IL‐10 at 6 months. Quartile‐based analysis demonstrated a dose–response association between ICAM‐1 and PTS. ICAM‐1 and IL‐10 were also associated with PTS severity. Analysis of biomarker trajectories after DVT demonstrated an association between the highest‐trajectory group of ICAM‐1 and PTS. Conclusions In this prospective study, ICAM‐1 over time was most consistently associated with the risk of PTS. Further study is required to confirm these findings and assess their potential clinical relevance.